The customer service connection - Kantola Productions (Mill Valley, CA : Kantola Productions, 1994)
Teaches essential customer service skills that win customer loyalty. Motivates customer service employees to serve as information resources for their organizations. Viewers learn both how to provide extraordinary service and how to identify and communicate essential information about customers
H-73089
Keywords: Customer services; Teams in the workplace -- Management